PREDIKSI VOLUME AKUIFER BEBAS DI KECAMATAN BUKIT RAYA DENGAN METODE BEDA HINGGA - Muhammad Juandi; Muhammad syahputra syahputra; Usman Malik (JOURNAL ONLINE OF PHYSICS, 2017)
A research about prediction of unconfined aquifer in Distrcit Bukit Raya have been done by using finite difference method. The depth of unconfined aquifer data using contour grid District Bukit Raya in 2015 solved numerically by using computer program MATLAB application R2009a version. The aim of this research was to analyze the effect of population growth on the volume of unconfined aquifer in District Bukit Raya. The result of the research could be informed to District Bukit Raya as follows : the total volume of underground water in 2017 in the amount of 10.399.615,33 m3 and in 2021 in the amount of 10.931.060,63 m3. the volume of underground water that taken by residents in 2017 were in the amount of 5.038.007,328m3and in 2021 were in the amount of 5.334.525,03 m3. The inreasing of lowering the volume of underground water (residue), so that in 2017 The inreasing of loweringthe volume of underground wateras much as5.361.608 m3and in 2021 as much as 5.596.535,6 m3. It can be concluded that the volume of underground waterinfluenced by the changes of the dept of aquifer and the large of green open space